Pengembangan Buku Cerita Wayang Bergambar (Buta Wagam) Untuk Siswa SD/MI - Novia Putri Wulandari; Maria Ulfa Y J; Ida Putriani (Universitas 45 Surabaya, 2023)
The development of this research is to make Javanese language learning more effective in elementary schools and change the mindset of elementary school students that learning Javanese, especially the wayang story chapter, is not difficult and even tends to be fun. The research development was carried out in order to overcome the problems of students who find it difficult to master Javanese vocabulary, retell the story of the Five Javanese Pandhawa wayang puppets coherently and correctly, mention who the wayang characters are in the story. This research was conducted with Research and Development. The initial process of creating story material and story illustrations is then validated by story experts, language experts and learning media experts. Then it was tested on small groups to determine the level of readability of the learning media for students and teachers, so that it could be concluded that the learning media for Javanese illustrated wayang story books could be used as a learning and literacy medium for elementary school students. The results of research and development of illustrated wayang storybooks for elementary school students have been completed in accordance with procedures according to Sugiyono which are limited to seven stages. At the story expert validation stage, the percentage score was 92.8%, which was considered very feasible, while for language validators it was 95.3%, which was considered very feasible, and finally, media validation had a percentage score of 92.7%, which was also assessed as very feasible. From the results of the third validation, the average value was 83.6%. This value falls into the 90%-100% range and is considered very feasible.